2019
DOI: 10.1103/physrevlett.122.237601
|View full text |Cite
|
Sign up to set email alerts
|

Topological Phase Transition in non-Hermitian Quasicrystals

Abstract: The discovery of topological phases in non-Hermitian open classical and quantum systems challenges our current understanding of topological order. Non-Hermitian systems exhibit unique features with no counterparts in topological Hermitian models, such as failure of the conventional bulk-boundary correspondence and non-Hermitian skin effect. Advances in the understanding of the topological properties of non-Hermitian lattices with translational invariance have been reported in several recent studies, however li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
277
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(291 citation statements)
references
References 75 publications
11
277
1
2
Order By: Relevance
“…On the other hand, for real-energy on-site potential disorder a non-Hermitian delocalization transition is observed * stefano.longhi@polimi.it by application of an imaginary gauge field (Hatano-Nelson-Anderson model [23-26, 29, 33, 39, 46, 47, 49]). Other studies focused on several non-Hermitian extensions of diagonal or off-diagonal AAH models [31, 35-37, 40, 41, 43, 44, 47-50], with either commensurate or incommensurate potential, showing the impact of non-Hermiticity terms in the Hamiltonian on edge states and parity-time (PT ) symmetry breaking [35-37, 41, 43], on the Hofstadter butterfly spectrum [36], and on the localization properties of eigenstates [43,44,[47][48][49][50]. Recently, the topological nature of a metal-insulator phase transition found in an incommensurate PT -symmetric AAH model has been revealed [48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for real-energy on-site potential disorder a non-Hermitian delocalization transition is observed * stefano.longhi@polimi.it by application of an imaginary gauge field (Hatano-Nelson-Anderson model [23-26, 29, 33, 39, 46, 47, 49]). Other studies focused on several non-Hermitian extensions of diagonal or off-diagonal AAH models [31, 35-37, 40, 41, 43, 44, 47-50], with either commensurate or incommensurate potential, showing the impact of non-Hermiticity terms in the Hamiltonian on edge states and parity-time (PT ) symmetry breaking [35-37, 41, 43], on the Hofstadter butterfly spectrum [36], and on the localization properties of eigenstates [43,44,[47][48][49][50]. Recently, the topological nature of a metal-insulator phase transition found in an incommensurate PT -symmetric AAH model has been revealed [48].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focused on several non-Hermitian extensions of diagonal or off-diagonal AAH models [31, 35-37, 40, 41, 43, 44, 47-50], with either commensurate or incommensurate potential, showing the impact of non-Hermiticity terms in the Hamiltonian on edge states and parity-time (PT ) symmetry breaking [35-37, 41, 43], on the Hofstadter butterfly spectrum [36], and on the localization properties of eigenstates [43,44,[47][48][49][50]. Recently, the topological nature of a metal-insulator phase transition found in an incommensurate PT -symmetric AAH model has been revealed [48]. Most of available results on localization and phase transition phenomena in non-Hermitian AAH models are based on numerical simulations, while few analytical and rigorous results are available owing to the extraordinary complexity of the spectral problem.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, point-gapped topological phases cannot always be continuously deformed into any Hermitian counterparts; topology for a point gap is intrinsic to non-Hermitian systems in sharp contrast to a line gap. A point gap describes unique non-Hermitian topological phenomena such as localization transitions [1,2,46,52,58] and emergence of exceptional points [21-26, 34, 37, 49, 50, 53, 55].A hallmark of topological phases is the presence of the localized states at the boundaries as a result of nontrivial topology of the bulk [61-63]. Remarkably, non-Hermiticity alters the nature of the bulk-boundary correspondence (BBC) .…”
mentioning
confidence: 99%
“…Then more complex models has been introduced and studied in the literature . In a recent paper, it was shown that topological phase can also arise in a non-Hermitian quasicrystal with parity-time symmetry [66]. Note that topological edge states in a non-Hermitian system can have real or complex energy eigenvalues.…”
Section: Introductionmentioning
confidence: 99%